2022
DOI: 10.1055/a-1926-0453
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells are Associated with Thromboembolic Events in Patients with Antiphospholipid Antibodies

Abstract: Background: Endothelium damage has been described in antiphospholipid antibodies (aPL) positive patients. However, it is uncertain whether circulating endothelial cells (CECs) – which are released when endothelial injury occurs – can identify patients at high risk for thrombosis. Methods: Ninety-seven patients with aPL and/or Systemic Lupus Erythematosus (SLE) were included. CECs were determined by an automated CellSearch® system. We also assayed plasma levels of tissue factor-bearing extracellular vesicles (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The stressed or injured endothelium releases CECs and extracellular vesicles, both of which are elevated in APS [29,30]. A 2022 study quantified CECs from the blood of patients with aPL and/or SLE and found that patients with a history of obesity, myocardial infarction, venous thromboembolism, or nephropathy had more CECs in circulation [31 ▪▪ ]. Additionally, the study also showed a significant correlation between CECs and other markers likely to be associated with endothelial dysfunction, including tissue factor-bearing extracellular vesicles and soluble TREM-1 (triggering receptor expressed on myeloid cells-1) [31 ▪▪ ].…”
Section: Endothelial Activation and Injurymentioning
confidence: 99%
“…The stressed or injured endothelium releases CECs and extracellular vesicles, both of which are elevated in APS [29,30]. A 2022 study quantified CECs from the blood of patients with aPL and/or SLE and found that patients with a history of obesity, myocardial infarction, venous thromboembolism, or nephropathy had more CECs in circulation [31 ▪▪ ]. Additionally, the study also showed a significant correlation between CECs and other markers likely to be associated with endothelial dysfunction, including tissue factor-bearing extracellular vesicles and soluble TREM-1 (triggering receptor expressed on myeloid cells-1) [31 ▪▪ ].…”
Section: Endothelial Activation and Injurymentioning
confidence: 99%